2007
DOI: 10.1002/asl.151
|View full text |Cite
|
Sign up to set email alerts
|

An explicit and conservative remapping strategy for semi‐Lagrangian advection

Abstract: A conservative semi-Lagrangian advection scheme has recently been proposed by Cotter et al. in their article "The remapped particle-mesh semi-Lagrangian advection scheme" published in The Quarterly Journal of the Royal Meteorological Society (2007, volume 133, pages 251-260). It is based on a remapped particle-mesh implementation using bicubic Bspline as basis functions. It has been shown that the method is of comparable accuracy as standard bicubic semi-Lagrangian advection schemes. A potential drawback of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…2. It uses a two-step Tracking Radar Echoes by Crosscorrelation (TREC) algorithm to estimate motion of a storm, and a mass-conserving, monotonic advection scheme based on the explicit remapped particle-mesh semi-Lagrangian (RPMSL) advection scheme for extrapolating reflectivity factor fields (Reich, 2007). The length step was chosen to be 5 min, corresponding to the temporal resolution of radar observations.…”
Section: Multi-scale Tracking and Forecasting Radar Echoes (Mtafre) Smentioning
confidence: 99%
“…2. It uses a two-step Tracking Radar Echoes by Crosscorrelation (TREC) algorithm to estimate motion of a storm, and a mass-conserving, monotonic advection scheme based on the explicit remapped particle-mesh semi-Lagrangian (RPMSL) advection scheme for extrapolating reflectivity factor fields (Reich, 2007). The length step was chosen to be 5 min, corresponding to the temporal resolution of radar observations.…”
Section: Multi-scale Tracking and Forecasting Radar Echoes (Mtafre) Smentioning
confidence: 99%
“…The LMCSL scheme is quite similar to the so‐called ‘Remapped particle‐mesh semi‐Lagrangian advection scheme’ by Cotter et al (2007) and even more so to the modified version of this scheme by Reich (2007). The original scheme by Cotter et al (2007) involves solution of an implicit set of linear equations which is needed to obtain modified weights analogue to those in but for a downstream trajectory SL scheme.…”
Section: Locally Mass Conserving Semi‐lagrangian Formulationmentioning
confidence: 99%
“…The original scheme by Cotter et al (2007) involves solution of an implicit set of linear equations which is needed to obtain modified weights analogue to those in but for a downstream trajectory SL scheme. In the modified scheme by Reich (2007) an explicit modification of the downstream weights are introduced. It is even demonstrated that the methodology may be modified to handle the upstream SL approach as used in this paper, however, only for the non‐divergent passive advection equations.…”
Section: Locally Mass Conserving Semi‐lagrangian Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This becomes problematic when low density or highly turbulent regions are studied. Hence, numerical methods which discretize the Vlasov equation on a grid of the phase space can offer a good alternative to PIC methods (see [7,16,17,34,6,12,28]). …”
Section: Contents 1 Introductionmentioning
confidence: 99%